Daily rhythm of rumination in the goat (Capra hircus) is not driven by feeding - Mohammed El Mehdi M’hani; Younes Beniaich; Hicham Farsi; Mohammed Piro; Mohamed Rachid Achaâban; Paul Pévet; Etienne Challet; Khalid El Allali (Scientific Reports)
Abstract Rumination shows a nocturnal rhythmic pattern in day-active ruminants. Although feeding has been shown to quantitatively modulate rumination, it is not clear yet if feeding rhythm plays a causal role in rumination rhythm. The present study was carried out to determine whether the daily rhythm of rumination in goats under natural environmental conditions is food-dependent or not, and whether it is modulated by the season. Rumination and locomotor activity (LA) were continuously monitored in four male Moroccan goats, fed once daily every morning, and then fasted for 4 days. The same experimental design was carried out in two different seasons (summer and winter). The results show that normally fed goats ruminate on average 281 ± 37 min in both seasons. Rumination shows a rhythmic 24-h profile with a late nocturnal peak. During the four-day food deprivation, rumination persisted while its total amount duration was significantly reduced in both seasons. Our results also illustrate the clear phase-opposition between the diurnal rhythm of LA and the nocturnal rhythm of rumination. This study characterized the daily rhythm rumination in goats according to seasons and fed/fasted states, and provided clear evidence that this rhythm is not generated by feeding behavior. Further investigations are required to determine whether rumination has an endogenous origin and is driven by the central circadian clock.